Cost‐effectiveness analysis of cytomegalovirus prophylaxis in allogeneic hematopoietic cell transplant recipients from a US payer perspective. Issue 6 (5th October 2020) - Alsumali, Adnan; Chemaly, Roy F.; Graham, Jonathan; Jiang, Yiling; Merchant, Sanjay; Miles, LaStella; Schelfhout, Jonathan; Yang, Joe; Tang, Yuexin
Abstract: To evaluate the cost‐effectiveness of letermovir versus no prophylaxis for the prevention of cytomegalovirus infection and disease in adult cytomegalovirus‐seropositive allogeneic hematopoietic cell transplantation (allo‐HCT) recipients. A decision model for 100 patients was developed to estimate the probabilities of cytomegalovirus infection, cytomegalovirus disease, various other complications, and death in patients receiving letermovir versus no prophylaxis. The probabilities of clinical outcomes were based on the pivotal phase 3 trial of letermovir use for cytomegalovirus prophylaxis versus placebo in adult cytomegalovirus‐seropositive recipients of an allo‐HCT. Costs of prophylaxis with letermovir and of each clinical outcome were derived from published sources or the trial clinical study reports. Incremental cost‐effectiveness ratios (ICERs) in terms of cost per quality‐adjusted life year (QALY) gained were used in the model. One‐way and probabilistic sensitivity analyses were conducted to explore uncertainty around the base‐case analysis. In this model, the use of letermovir prophylaxis would lead to an increase of QALYs (619) and direct medical cost (1 733 794) compared with no prophylaxis (578 QALYs; 710 300) in cytomegalovirus‐seropositive recipients of an allo‐HCT. Letermovir use for cytomegalovirus prophylaxis was a cost‐effective option versus no prophylaxis with base‐case analysis ICER 25 046/QALY gained. One‐way sensitivity analysis showed the most influential parameter was mortality rate. The probabilistic sensitivity analysis showed a 92% probability of letermovir producing an ICER below the commonly accepted willingness‐to‐pay threshold of 100 000/QALY gained. Based on this model, letermovir use for cytomegalovirus prophylaxis was a cost‐effective option in adult cytomegalovirus‐seropositive recipients of an allo‐HCT. Highlights: letermovir prophylaxis lead to better healthcare outcomes and higher direct medical costs compared with no prophylaxis. letermovir prophylaxis is cost‐effective option versus no prophylaxis in adult cytomegalovirus‐seropositive recipients of an allo‐HCT, with incremental cost‐effectiveness ratios below 30, 000 per quality‐adjusted life‐year gained.